Piezoelectric laminate and piezoelectric element
Patent Information
- Application Number
- JP2021141806
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-08-31
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2041-08-31
AI Technical Summary
【0017】 本開示の圧電積層体及び圧電素子によれば、圧電特性の低下を抑制することが可能であり、かつ、製造コストを抑制することができる。
Smart Images

Figure 0007636302000002 
Figure 0007636302000003 
Figure 0007636302000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a piezoelectric laminate and a piezoelectric element. [Background technology]
[0002] Perovskite oxides such as lead zirconate titanate (Pb(Zr,Ti)O3, hereafter referred to as PZT) are known as materials with excellent piezoelectric and ferroelectric properties. Piezoelectrics made of perovskite oxides are used as piezoelectric films in piezoelectric elements that have a lower electrode, a piezoelectric film, and an upper electrode on a substrate. These piezoelectric elements are being developed into various devices such as memories, inkjet heads (actuators), micromirror devices, angular velocity sensors, gyro sensors, ultrasonic elements (PMUT: Piezoelectric Micromachined Ultrasonic Transducers), and vibration power generation devices.
[0003] The piezoelectric properties of perovskite oxides change significantly depending on the excess or deficiency of oxygen in the perovskite structure. In particular, oxygen is easily released from perovskite oxides containing Pb, such as PZT films, and oxygen defects are generated in the piezoelectric film, which tends to cause deterioration in the piezoelectric properties and durability. In order to suppress oxygen release from perovskite oxides, it is effective to use conductive oxides such as SRO (SrRuO3) and IrO2 in the regions of the lower and upper electrodes that contact the piezoelectric film. When using a conductive oxide in the region that contacts the piezoelectric film, it is common to stack an electrode layer made of a precious metal layer such as Pt or Ir in order to ensure good conductivity (see, for example, Patent Document 1).
[0004] Patent Document 2, which relates to a piezoelectric element having a PZT film, proposes that the lower electrode be configured so that the conductive oxide is more abundant on the substrate side and the conductive metal is more abundant on the piezoelectric film side in order to improve adhesion at each interface between the substrate and the lower electrode, and between the lower electrode and the piezoelectric film. It also describes that Pt group is preferable as the conductive metal contained in the lower electrode. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2018-085478 A [Patent Document 2] JP 2007-300071 A Summary of the Invention [Problem to be solved by the invention]
[0006] As described in Patent Document 1, in a piezoelectric element having a piezoelectric film of a perovskite oxide, a decrease in piezoelectric characteristics can be suppressed by providing a conductive oxide layer on the piezoelectric film side of the electrode layer. Also, as described in Patent Documents 1 and 2, a precious metal of the Pt group is generally used for the lower electrode.
[0007] However, since platinum group metals are very expensive, there is a problem in that the manufacturing costs of piezoelectric elements having electrodes containing platinum group metals cannot be sufficiently reduced.
[0008] The technology disclosed herein has been made in consideration of the above circumstances, and aims to provide a piezoelectric laminate and a piezoelectric element that are capable of suppressing deterioration of piezoelectric characteristics and reducing manufacturing costs. [Means for solving the problem]
[0009] The piezoelectric laminate of the present disclosure is a piezoelectric laminate including a lower electrode layer and a piezoelectric film including a perovskite oxide, in this order, on a substrate, the lower electrode layer includes a metal layer containing Ni and a surface layer containing Ni oxide or Ni oxynitride; In the lower electrode layer, the surface layer is disposed closest to the piezoelectric film.
[0010] In the piezoelectric laminate of the present disclosure, it is preferable that the content of Ni element in the thickness direction of the surface layer increases from the piezoelectric film side to the metal layer, the change in the content of Ni element is continuous, and the change in the content of Ni element from the surface layer to the metal layer is continuous.
[0011] In the piezoelectric laminate of the present disclosure, the thickness of the surface layer is preferably 20 nm to 60 nm.
[0012] In the piezoelectric laminate of the present disclosure, it is preferable to provide an orientation control layer between the lower electrode layer and the piezoelectric film, the orientation control layer containing a metal oxide other than Ni oxide, wherein the metal oxide preferably contains at least one of Sr and Ba.
[0013] In the piezoelectric laminate of the present disclosure, the perovskite oxide preferably contains Pb, Zr, Ti and O.
[0014] In the piezoelectric laminate of the present disclosure, the perovskite oxide preferably contains at least one of Nb, Sc, and Ni.
[0015] In the piezoelectric laminate of the present disclosure, the perovskite oxide is preferably a compound represented by the following general formula (1). Pb{(Zr x Ti 1-x ) 1-y Nb y}O3(1) 0 <x<1、0.1≦y≦0.4、
[0016] A piezoelectric element according to the present disclosure includes the piezoelectric stack according to the present disclosure and an upper electrode layer provided on the piezoelectric film of the piezoelectric stack. Effect of the Invention
[0017] According to the piezoelectric laminate and piezoelectric element of the present disclosure, it is possible to suppress the deterioration of the piezoelectric characteristics and to suppress the manufacturing costs. [Brief description of the drawings]
[0018] [Figure 1] 1 is a cross-sectional view showing a layer structure of a piezoelectric laminate and a piezoelectric element according to a first embodiment. [Diagram 2] 5 is a cross-sectional view showing a layer structure of a piezoelectric laminate and a piezoelectric element according to a second embodiment. FIG. [Diagram 3] 3 is a diagram showing a profile of the content of Ni element and O element in the thickness direction of the lower electrode layer in the piezoelectric element shown in FIG. 2. [Figure 4] 3 is a diagram showing another profile of the Ni element content in the thickness direction of the lower electrode layer in the piezoelectric element shown in FIG. 2. [Diagram 5] FIG. 11 is a cross-sectional view showing a layer structure of a piezoelectric laminate and a piezoelectric element according to a third embodiment. [Figure 6] 13 is a diagram showing the profiles of the Ni element and O element contents in the thickness direction of the lower electrode layer of Example 2. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In the drawings, the thicknesses and ratios of each layer are appropriately changed for ease of viewing, and do not necessarily reflect the actual thicknesses and ratios.
[0020] "Piezoelectric laminate 5 and piezoelectric element 1 according to the first embodiment" Fig. 1 is a cross-sectional schematic diagram showing the layer structure of a piezoelectric stack 5 of a first embodiment and a piezoelectric element 1 including the piezoelectric stack 5. As shown in Fig. 1, the piezoelectric element 1 includes a piezoelectric stack 5 and an upper electrode layer 18. The piezoelectric stack 5 includes a substrate 10, and a lower electrode layer 12 and a piezoelectric film 15 that are laminated on the substrate 10. Here, "lower" and "upper" do not mean up and down in the vertical direction, but simply refer to the electrode disposed on the substrate 10 side across the piezoelectric film 15 as the lower electrode layer 12 and the electrode disposed on the opposite side of the piezoelectric film 15 to the substrate 10 as the upper electrode layer 18.
[0021] In the piezoelectric laminate 5, the lower electrode layer 12 includes a metal layer 12c containing Ni and a surface layer 12b containing Ni oxide or Ni oxynitride. In the lower electrode layer 12, the surface layer 12b is disposed closest to the piezoelectric film 15. In this example, the surface layer 12b and the piezoelectric film 15 are formed in contact with each other, and Ni oxide or Ni oxynitride is present at the boundary 12a between them.
[0022] The term "metal layer" refers to a layer whose constituent elements are composed only of metal species, excluding inevitable impurities, and specifically refers to a layer in which 95 at% or more of the constituent elements are metal elements. The term "metal layer containing Ni" refers to the metal layer 12c containing Ni element as the main component. Here, the main component means 50 at% or more. In the surface layer 12b containing Ni oxide or Ni oxynitride, the main component of the metal species among the elements constituting the surface layer 12b is Ni element. Examples of metal species other than Ni contained in the lower electrode layer 12 include Cu, Al, Ti, Ta, Cr, and Fe. However, if the metal species contained in the lower electrode layer 12 is only Ni element, the number of material species can be reduced and the manufacturing method can be simplified, which is preferable.
[0023] The surface layer 12b also contains Ni as a main component of the metal species, and this Ni may be entirely oxidized or oxynitrided, or may contain a mixture of Ni that is not oxidized or oxynitrided and Ni oxide or Ni oxynitride. However, it is preferable that 20 at% or more of the Ni present in the surface layer 12b is oxidized or oxynitrided, and it is more preferable that 30 at% or more of the Ni is oxidized or oxynitrided.
[0024] The thickness t of the lower electrode layer 12 is preferably about 50 nm to 300 nm, more preferably 100 nm to 300 nm. The lower electrode layer 12 preferably contains Ni oxide or Ni oxynitride over a range of 20 nm or more from the side closest to the piezoelectric film 15, and more preferably contains Ni oxide or Ni oxynitride over a range of 30 nm or more from the side closest to the piezoelectric film 15. In order to ensure sufficient conductivity without making the thickness t of the lower electrode layer 12 too thick, the range containing Ni oxide is preferably 60 nm or less from the side closest to the piezoelectric film 15. That is, the lower electrode layer 12 preferably contains Ni oxide or Ni oxynitride over a range of 20 nm to 60 nm from the side closest to the piezoelectric film 15, and more preferably 40 nm to 60 nm. Therefore, the thickness t1 of the surface layer 12b is preferably 20 nm to 60 nm, and more preferably 40 nm to 60 nm. The thickness t2 of the metal layer 12c of the lower electrode layer 12 is preferably 50 nm to 200 nm, and more preferably 80 nm to 150 nm. The thickness can be estimated from a cross-sectional scanning electron microscope (SEM) image, a transmission electron microscope (TEM) or a SIMS (Secondary Ion Mass Spectrometry) analysis.
[0025] The piezoelectric film 15 contains a perovskite oxide. The perovskite oxide preferably accounts for 80 mol % or more of the piezoelectric film 15. Furthermore, the piezoelectric film 15 is preferably made of a perovskite oxide (however, it contains inevitable impurities).
[0026] Perovskite oxides are represented by the general formula ABO3. In the general formula, A is an A-site element and is one or a combination of two or more of Pb, Ba (barium), La (lanthanum), Sr, Bi (bismuth), Li (lithium), Na (sodium), Ca (calcium), Cd (cadmium), Mg (magnesium), and K (potassium). In the general formula, B is a B-site element, which is one or a combination of two or more of Ti, Zr, V (vanadium), Nb, Ta, Cr (chromium), Mo (molybdenum), W (tungsten), Mn (manganese), Fe (iron), Ru, Co (cobalt), Ir, Ni (nickel), Cu (copper), Zn (zinc), Ga (gallium), In, Sn, antimony (Sb), and lanthanide elements. In the general formula, O is oxygen. For A:B:O, the standard is 1:1:3, but it may deviate within the range where a perovskite structure can be obtained.
[0027] The piezoelectric film 15 preferably contains Pb as the main component of the A site. In this specification, "main component" means a component that occupies 50 mol% or more. That is, "containing Pb as the main component of the A site" means that 50 mol% or more of the components in the A-site elements are Pb. The other elements in the A site and the B-site elements other than Pb in the perovskite-type oxide containing Pb are not particularly limited.
[0028] The perovskite-type oxide is preferably a lead zirconate titanate (PZT) system containing Pb (lead), Zr (zirconium), Ti (titanium), and O (oxygen).
[0029] In particular, it is preferable that the perovskite-type oxide is a compound represented by the following general formula (P) containing an additive B1 at the B site of PZT. Pb{(Zr x Ti 1-x ) 1-y B1 y}O3 (P) Here, 0 < x < 1 and 0 < y < 0.3. In the general formula (P), Pb:{(Zr x Ti 1+x ) 1-y B y}:O has a standard of 1:1:3, but it may deviate within the range where a perovskite structure can be obtained.
[0030] Examples of B1 include Sc (scandium), V, Nb, Ta, Cr, Mo, W, Mn, Fe, Ru, Co, Ir, Ni, Cu, Zn, Ga, In, Sn, and Sb, and it is preferable that B1 contains one or more of these elements. It is more preferable that B1 is any one of Sc, Nb, and Ni.
[0031] In particular, it is preferable that B1 is Nb, and the perovskite oxide contains Nb, and is preferably a compound represented by the following general formula (1). Pb{(Zr x Ti 1-x ) 1-y Nb y}O3(1) 0 <x<1、0.1≦y≦0.4、
[0032] The thickness of the piezoelectric film 15 is not particularly limited and is usually 200 nm or more, for example, 0.2 μm to 5 μm. The thickness of the piezoelectric film 15 is preferably 1 μm or more.
[0033] The substrate 10 is not particularly limited, and examples thereof include substrates of silicon, glass, stainless steel, yttrium-stabilized zirconia, alumina, sapphire, silicon carbide, etc. The substrate 10 may be a laminated substrate in which a SiO2 oxide film is formed on the surface of a silicon substrate.
[0034] The upper electrode layer 18 is an electrode that is paired with the lower electrode layer 12 and applies a voltage to the piezoelectric film 15. The main component of the upper electrode layer 18 is not particularly limited, and examples thereof include metals or metal oxides such as gold (Au), platinum (Pt), iridium (Ir), ruthenium (Ru), titanium (Ti), molybdenum (Mo), tantalum (Ta), aluminum (Al), copper (Cu), silver (Ag), chromium (Cr), and zinc (Zr), and combinations thereof. In addition, the upper electrode layer 18 may be made of ITO (indium tin oxide), IGZO, LaNiO3, and SRO (which may contain Ba). The upper electrode layer 18 may be a single layer or a laminated structure made of multiple layers. From the viewpoint of suppressing oxygen diffusion from the piezoelectric film 15, it is preferable that at least the region of the upper electrode layer 18 that contacts the piezoelectric film is an oxide electrode.
[0035] The thickness of the upper electrode layer 18 is not particularly limited, but is preferably about 50 nm to 300 nm, and more preferably 100 nm to 300 nm.
[0036] As described above, in the piezoelectric laminate 5 and the piezoelectric element 1 of this embodiment, the lower electrode layer 12 includes a metal layer 12c containing Ni and a surface layer 12b containing Ni oxide or Ni oxynitride, and in the lower electrode layer 12, the surface layer 12b is disposed closest to the piezoelectric film 15. When the region of the lower electrode layer 12 closest to the piezoelectric film 15 is a metal layer, oxygen in the piezoelectric film 15 may escape and move to the lower electrode layer 12 side. Loss of oxygen in the piezoelectric film 15 leads to a decrease in piezoelectric characteristics and a decrease in long-term reliability (durability). However, in the piezoelectric laminate 5 and the piezoelectric element 1 of this embodiment, the surface layer 12b containing Ni oxide or Ni oxynitride is disposed closest to the piezoelectric film 15, so that loss of oxygen in the piezoelectric film 15 can be suppressed, and as a result, a decrease in piezoelectric characteristics and a decrease in long-term reliability can be suppressed.
[0037] Furthermore, since Ni is used as the metal species in the constituent elements of lower electrode layer 12, the manufacturing costs can be significantly reduced compared to conventional piezoelectric elements that use a Pt group metal as the main component.
[0038] In addition, according to the findings of the present inventors, when an electrode layer made of Ir is used as the lower electrode layer, the adhesion to the substrate is low, so that in practical use, an adhesion layer such as TiW is essential before depositing Ir on the substrate. However, as in this embodiment, when the lower electrode layer 12 is provided with the Ni metal layer 12c on the substrate 10 side, sufficient adhesion can be ensured without providing an adhesion layer. In other words, if the Ni metal layer 12c is configured to be in contact with the substrate, an adhesion layer is not necessary, and the manufacturing cost can be further reduced.
[0039] If the thickness of surface layer 22b of lower electrode layer 12 is 20 nm to 60 nm, the effect of suppressing the occurrence of oxygen defects in piezoelectric film 15 can be further improved, and deterioration of piezoelectric characteristics and long-term reliability can be further suppressed.
[0040] "Piezoelectric laminate and piezoelectric element according to the second embodiment" Fig. 2 is a schematic cross-sectional view of a piezoelectric laminate 5A according to a second embodiment and a piezoelectric element 1A including the piezoelectric laminate 5A. In Fig. 2, components equivalent to those of the piezoelectric laminate 5 and the piezoelectric element 1 according to the first embodiment shown in Fig. 1 are denoted by the same reference numerals and detailed description thereof will be omitted.
[0041] A piezoelectric stack 5A and a piezoelectric element 1A of the second embodiment have a lower electrode layer 22 having a different configuration from the piezoelectric stack 5 and the piezoelectric element 1 and the lower electrode layer 12 of the first embodiment.
[0042] In the piezoelectric laminate 5A and the piezoelectric element 1A of this embodiment, the content of Ni element in the thickness direction of the surface layer 12b changes in an increasing manner from the side closest to the piezoelectric film 15 toward the metal layer 22c, and the change in the content of Ni element in the thickness direction is continuous. Also, the change in the content from the surface layer 12b to the metal layer 12c is continuous. Here, the "content of Ni element in the thickness direction" is the ratio of Ni element to all elements at each position in the thickness direction, and is expressed in at%. The "thickness direction" is the direction perpendicular to the substrate 10. The "change in the content is continuous" means that there is no discontinuous portion in the content profile in the thickness direction (see FIG. 2). In the lower electrode layer 22, among the constituent elements constituting the lower electrode layer 22 other than Ni element, the content of elements whose content in the entire region of the lower electrode layer 22 is 10 at% or more is preferably constant or changes continuously in the thickness direction.
[0043] The enlarged view of FIG. 2 shows a schematic diagram of the change in the Ni element content in lower electrode layer 22. In the enlarged view of FIG. 2, the greater the Ni element content, the darker the color, and the smaller the content, the lighter the color. FIG. 3 shows the change in the Ni element and O element content in lower electrode layer 22 in the thickness direction (content profile). The horizontal axis shows the position in the thickness direction of lower electrode layer 22. 0 on the horizontal axis is the position of lower electrode layer 22 closest to piezoelectric film 15 (boundary 22a), and the position of the two-dot chain line is the boundary with substrate 10.
[0044] As shown in Fig. 3, in this embodiment, the lower electrode layer 22 contains Ni element throughout the entire thickness direction. In the thickness direction of the surface layer 22b, the Ni element content increases from the boundary 22a with the piezoelectric film 15, which is closest to the piezoelectric film 15, to the metal layer 22c. The Ni element content from the surface layer 22b to the metal layer 22c changes continuously. More specifically, the Ni element content increases monotonically from the boundary 22a closest to the piezoelectric film 15 of the surface layer 22b to the metal layer 22c of the surface layer 22b, and increases until it reaches the Ni element content of the metal layer 22c. In this embodiment, the Ni element content in the metal layer 22c is approximately constant in the thickness direction and is approximately 100 at%. Here, the term "increasing trend" refers to an overall increasing tendency, such as when comparing the starting point and the ending point, the content is higher at the end point than at the starting point, and for example, as shown in Fig. 3, in a content profile with the piezoelectric film 15 side on the left and the substrate 10 side on the right, even if there are some points where the content drops beyond the measurement error, the overall trend is upward to the right, which is included in the increasing trend. Also, "monotonically increasing" refers to an increase in the content profile without including any points where the content drops beyond the measurement error.
[0045] The preferred ranges of the thicknesses of the lower electrode layer 22, the surface layer 22b, and the metal layer 22c in this embodiment are the same as the preferred ranges of the thickness t of the lower electrode layer 12, the thickness t1 of the surface layer 12b, and the thickness t2 of the metal layer 12c in the first embodiment described above. However, since the content of Ni element changes continuously from the surface layer 22b to the metal layer 22c, the boundary 22d between the surface layer 22b and the metal layer 22c in the lower electrode layer 22 is not clear in, for example, a scanning electron microscope image. Therefore, the thicknesses t1 and t2 of the surface layer 22b and the metal layer 22c are determined from the composition distribution in the thickness direction of the lower electrode layer 22, that is, the measurement data of the content change of the constituent elements (see Figures 3 and 6). Specifically, in the profile shown in Figure 3 or Figure 6, the region where the O element (or the O element and the N element) shows a constant value at the lowest value (almost 0 at%) is regarded as the metal layer 22c.
[0046] The elemental content in the lower electrode layer 22 and the change in the elemental content in the thickness direction can be measured by SIMS (Secondary Ion Mass Spectrometry) analysis. In this disclosure, the elemental content is a value measured by SIMS. In addition, in actual measurement data, the content varies by about ±5 at% due to noise, so the variation of about ±5 at% is considered to be within the range of measurement error.
[0047] In this embodiment, the lower electrode layer 22 is composed of Ni and O (oxygen) (including unavoidable impurities), and the profile showing the change in the content of O element in the thickness direction of the surface layer 22b of the lower electrode layer 22 is symmetrical to the profile showing the change in the content of Ni element with respect to the line of 50 at% content as the axis of symmetry. That is, it continuously decreases from the boundary 22a, which is closest to the piezoelectric film 15, toward the metal layer 22c side, and then shows a constant value of approximately 0 at%. Note that if the surface layer 22b contains Ni oxynitride, and the profile of the Ni content is as shown in FIG. 3, the profile of the total content of the O element content and the N element content will be similar to the profile of the O element shown in FIG. 3.
[0048] In the embodiment shown in FIG. 3, an example is shown in which almost all Ni is oxidized at the boundary 22a between the lower electrode layer 22 and the piezoelectric film 15. However, at the boundary 22a, oxidized Ni or oxynitrided Ni may be mixed with Ni that is not oxidized or oxynitrided. However, it is preferable that 20 at% or more of the Ni present at the boundary 22a is oxidized or oxynitrided, and more preferably 30 at% or more is oxidized or oxynitrided. Moreover, in the entire surface layer 22b, it is preferable that 20 at% or more of the Ni element is oxidized or oxynitrided, and more preferably 30 at% or more is oxidized or oxynitrided.
[0049] As described above, in the piezoelectric laminate 5A and piezoelectric element 1A of this embodiment, similarly to the piezoelectric laminate 5 and piezoelectric element 1 of the first embodiment, the lower electrode layer 22 includes a metal layer 22c containing Ni element and a surface layer 22b containing Ni oxide or Ni oxynitride, and in the lower electrode layer 22, the surface layer 22b is disposed closest to the piezoelectric film 15. Therefore, it is possible to suppress oxygen loss from the piezoelectric film 15, and as a result, it is possible to suppress deterioration of the piezoelectric characteristics and deterioration of long-term reliability.
[0050] Furthermore, since Ni is used as the metal type of the lower electrode layer 22, the manufacturing cost can be significantly reduced compared to conventional piezoelectric elements that use a Pt group metal as the main component.
[0051] Furthermore, in the piezoelectric laminate 5A and the piezoelectric element 1A of this embodiment, the Ni element content in the lower electrode layer 22 changes in a continuous manner in the thickness direction of the surface layer 22b from the side closest to the piezoelectric film 15 to the metal layer 22c, and the change in content is continuous. Also, the change in content from the surface layer 22b to the metal layer 22c is continuous. If the change in the Ni element content in the thickness direction is discontinuous, the adhesion may decrease at the discontinuous places and peeling may occur. However, as in this embodiment, if the change in the Ni element content in the surface layer 22b of the lower electrode layer 22 and in the part from the surface layer 22b to the metal layer 22c is continuous, the occurrence of peeling can be suppressed. In the region of the lower electrode layer 22 closest to the piezoelectric film 15, the closer the content ratio of Ni to O is to NiO, which is the stoichiometric ratio of Ni oxide, that is, 1:1, the higher the effect of suppressing oxidation. On the other hand, the higher the proportion of unoxidized metal Ni in the lower electrode layer 22, the higher the electrical conductivity and the higher the functionality of the lower electrode layer 22. Therefore, as in this embodiment, if the content of Ni element increases from the piezoelectric film 15 side to the metal layer 22c side, the effect of suppressing the occurrence of oxygen defects in the piezoelectric film 15 can be enhanced, and the effect of suppressing the decrease in conductivity can also be enhanced.
[0052] Furthermore, when the content of Ni element monotonically increases from the piezoelectric film 15 side, as in the piezoelectric laminate 5A and piezoelectric element 1A of the above embodiment, the effect of suppressing the occurrence of oxygen defects in the piezoelectric film 15 and the effect of suppressing the decrease in conductivity can be further enhanced.
[0053] As described above, in the piezoelectric laminate 5A and the piezoelectric element 1A of the above embodiment, the change in the Ni element content in the thickness direction of the lower electrode layer 22 is as shown in Fig. 3. However, the change in the Ni element content in the thickness direction of the lower electrode layer 22 is not limited to that shown in Fig. 3.
[0054] Fig. 4 shows other examples (profiles a to c) of the change in the Ni element content in the thickness direction of surface layer 22b of lower electrode layer 22. In Fig. 4, similar to Fig. 3, the horizontal axis indicates the position in the thickness direction of lower electrode layer 22. 0 on the horizontal axis is the position of lower electrode layer 22 closest to piezoelectric film 15 (boundary 22a), and the dashed double-dashed line position is the boundary with substrate 10. Although not shown in Fig. 4, the O element profiles are, for example, symmetrical with respect to the Ni element profiles and the 50 at % line as the central axis.
[0055] 4, the Ni element content in the thickness direction of surface layer 22b is about 50 at % at boundary 22a with piezoelectric film 15, gradually increases toward metal layer 22c, reaches a peak value, then decreases once, and may further increase at the boundary with metal layer 22c so as to match the content in metal layer 22c. Since the Ni element content at boundary 22d with metal layer 22c, which is the end point, is higher than that at boundary 22a with piezoelectric film 15, which is the start point, profile a can be said to change with an increasing trend from piezoelectric film 15 toward metal layer 22c.
[0056] Furthermore, as shown in profile b of Figure 4, the Ni element content in the thickness direction of surface layer 22b may be approximately 50 at % at boundary 22a with piezoelectric film 15, show a constant value for a while from boundary 22a toward metal layer 22c, and then monotonically increase to match the content in metal layer 22c at the boundary with metal layer 22c.
[0057] In the above-described embodiment and profiles a and b, the Ni element content is approximately 50 at% at the portion of lower electrode layer 22 closest to piezoelectric film 15. When lower electrode layer 22 is composed of Ni elements and O elements, if Ni elements are completely nitrided at boundary 22a on the piezoelectric film 15 side, the Ni element content is 50 at% and the O element content is 50 at%. In this case, there is no unoxidized Ni element, so the occurrence of oxygen defects in piezoelectric film 15 is highly suppressed.
[0058] However, as shown in profile c in Fig. 4, the Ni element content at boundary 22a of lower electrode layer 22 closest to piezoelectric film 15 is not limited to 50 at% and may be greater than 50 at%. Also, as shown in profile c in Fig. 4, the Ni element content may once decrease from the closest to piezoelectric film 15 toward metal layer 22c to a content lower than the Ni element content at boundary 22a, and then increase at the boundary with metal layer 22c to match the content in metal layer 22c.
[0059] In any of the profiles a to c, the lower electrode layer 22 includes a metal layer 22c containing Ni element and a surface layer 22b containing Ni nitride, and the surface layer 22b is disposed closest to the piezoelectric film 15. Therefore, the occurrence of oxygen defects in the piezoelectric film can be suppressed, and the effect of preventing the deterioration of the piezoelectric characteristics and improving long-term reliability can be obtained. In addition, in any of the profiles a to c, the content of Ni element in the lower electrode layer 22 changes in an increasing manner in the thickness direction of the surface layer 22b from the side closest to the piezoelectric film 15 to the metal layer 22c, and the change in the content is continuous, and the change in the Ni content from the surface layer 22b to the metal layer 22c is continuous. Therefore, the occurrence of peeling can be suppressed, the effect of suppressing the occurrence of oxygen defects in the piezoelectric film 15 can be enhanced, and the effect of suppressing the decrease in conductivity can be enhanced.
[0060] In the above embodiments, the content of Ni element in the metal layer 12c or 22c has been described as being constant in the thickness direction, but the content of Ni element in the metal layer 12c or 22c may vary in the thickness direction. In this case, the content of metal species other than Ni element increases or decreases with the change in the content of Ni element.
[0061] "Piezoelectric laminate 5B and piezoelectric element 1B according to the third embodiment" Fig. 5 is a cross-sectional schematic diagram of a piezoelectric laminate 5B according to the second embodiment and a piezoelectric element 1B including the piezoelectric laminate 5B. In Fig. 5, components equivalent to those of the piezoelectric laminates 5, 5A and piezoelectric elements 1, 1A according to the first and second embodiments shown in Figs. 1 and 2 are designated by the same reference numerals and detailed description thereof will be omitted.
[0062] 5, the piezoelectric stack 5B and the piezoelectric element 1B include an adhesion layer 11 between the substrate 10 and the lower electrode layer 22. In addition, an orientation control layer 13 is included between the lower electrode layer 22 and the piezoelectric film 15.
[0063] The adhesion layer 11 is provided to improve adhesion and suppress peeling between the substrate 10 and the lower electrode layer 22. As the adhesion layer 11, Ti, W, TiW or the like is suitably used.
[0064] The orientation control layer 13 is formed on the lower electrode layer 22. The orientation control layer 13 is a layer provided to suppress the occurrence of a pyrochlore phase that is likely to form in the initial stage of film formation of the piezoelectric film 15, and to obtain a good perovskite-type oxide. The orientation control layer 13 contains a metal oxide different from Ni oxide. The metal oxide preferably contains at least one of Sr and Ba.
[0065] In addition, as the orientation control layer 13, it is preferable to use a growth control layer described in, for example, WO 2020 / 250591, WO 2020 / 250632, and JP 2020-202327 A. That is, the orientation control layer 13 preferably contains a metal oxide represented by the following general formula (2). Ma dMb 1-d O e (2) Ma is one or more metal elements that can be substituted at the A site of the perovskite-type oxide, Mb consists of metal species that can be substituted at the B site of the perovskite-type oxide, with one of Sc, Zr, V, Ta, Cr, Mo, W, Mn, Fe, Ru, Co, Ir, Ni, Cu, Zn, Cd, Ga, In, and Sb as the main component, O is an oxygen element. Also, here, d and e respectively represent the composition ratios, 0 < d < 1, and e varies depending on the valences of Ma and Mb.
[0066] Specific examples of the orientation control layer 13 include BaRuO3 and SrRuO3.
[0067] The thickness of the orientation control layer 13 is preferably 2 nm or more and 20 nm or less, and more preferably about 10 nm.
[0068] That is, the piezoelectric laminate 5B and the piezoelectric element 1B of the present embodiment are the same as the piezoelectric laminate 5 and the piezoelectric element 1 of the first embodiment in that the lower electrode layer 22 includes a metal layer 22c containing Ni element and a surface layer 22b containing Ni oxide or Ni oxynitride. In the lower electrode layer 22, the surface layer 22b is disposed on the side closest to the piezoelectric film 15. Therefore, oxygen depletion of the piezoelectric film 15 can be suppressed, and as a result, deterioration of piezoelectric characteristics and long-term reliability can be suppressed. Further, since Ni is used as the metal species of the lower electrode layer 22, the manufacturing cost can be significantly reduced as compared with conventional piezoelectric elements using a metal of the Pt group as the main component.
[0069] In the piezoelectric laminate 5B and the piezoelectric element 1B of this embodiment, the configuration of the lower electrode layer 22 is the same as that of the piezoelectric laminate 5A and the piezoelectric element 1A of the second embodiment. Therefore, the Ni element content in the lower electrode layer 22 changes continuously, so that the occurrence of peeling can be suppressed. In addition, the Ni element content increases from the piezoelectric film 15 side toward the substrate 10 side, so that the effect of suppressing the occurrence of oxygen defects in the piezoelectric film 15 can be enhanced, and the effect of suppressing the decrease in conductivity can be enhanced. Furthermore, the Ni element content increases monotonically from the piezoelectric film 15 side, so that the effect of suppressing the occurrence of oxygen defects in the piezoelectric film 15 and the effect of suppressing the decrease in conductivity can be further enhanced.
[0070] Furthermore, the piezoelectric laminate 5B and piezoelectric element 1B of this embodiment are provided with the orientation control layer 13, and the piezoelectric film 15 is formed on the orientation control layer 13, so that it is possible to suppress the occurrence of the pyrochlore phase that is likely to form in the early stages of film formation. Since it is possible to suppress the occurrence of the pyrochlore phase at the interface of the piezoelectric film 15 on the lower electrode layer 22 side, the piezoelectric properties of the piezoelectric film 15 are good, and it is possible to obtain a higher dielectric constant and a higher piezoelectric constant than when the orientation control layer 13 is not present.
[0071] The piezoelectric elements 1, 1A, 1B or piezoelectric laminates 5, 5A, 5B of the above-described embodiments are applicable to ultrasonic devices, mirror devices, sensors, memories, and the like. EXAMPLES
[0072] Specific examples and comparative examples of the piezoelectric element of the present disclosure will be described below. First, the method of manufacturing the piezoelectric element of each example will be described. Note that conditions other than the configuration of the lower electrode layer and the presence or absence of an orientation control layer were common to each example. An RF (Radio frequency) sputtering device was used to deposit each layer.
[0073] (Production method) -substrate- A 6-inch silicon wafer with a thermal oxide film was used as the substrate.
[0074] -Lower electrode layer- A lower electrode layer was formed on the thermal oxide film of the substrate under the following film forming conditions in each example.
[0075] [Comparative Example 1] Before forming the lower electrode layer, a 20 nm thick TiW film was formed on the thermal oxide film of the substrate as an adhesive layer. Then, a 150 nm thick Ir film was formed on the TiW layer as a lower electrode layer under the conditions of Ar gas 60 sccm, RF power 300 W, and film formation pressure 0.25 Pa. The substrate temperature during the formation of the TiW and Ir layers was 350°C.
[0076] [Comparative Example 2] Under conditions of Ar gas 60 sccm, RF power 300 W, film formation pressure 0.25 Pa, and substrate temperature 350° C., a Ni film was formed to a thickness of 150 nm as a lower electrode layer.
[0077] [Example 1] A 100 nm Ni film was formed as a metal layer under conditions of Ar gas 60 sccm, RF power 300 W, deposition pressure 0.25 Pa, and substrate temperature 350°C. Subsequently, a 50 nm Ni oxide (NiO) film was formed as a surface layer on the Ni layer under conditions of Ar gas 30 sccm, O2 gas 30 sccm, RF power 500 W, and deposition pressure 0.25 Pa. In other words, a lower electrode layer with a two-layer structure was formed, with a metal layer made of Ni and a surface layer made of NiO layer provided on top of it. In Table 1, the layer configuration of the lower electrode layer is listed in the order of surface layer / metal layer.
[0078] [Examples 2, 4 to 7] Under the conditions of Ar gas 60 sccm, RF power 300 W, deposition pressure 0.25 Pa, and substrate temperature 350° C., a 100 nm Ni film was formed as a metal layer. Subsequently, on the Ni layer, the Ar gas was gradually reduced from 60 sccm to 30 sccm, and at the same time, the O2 gas was gradually increased from 0 sccm to 30 sccm, while a 50 nm Ni oxide film was formed under the conditions of RF power 500 W and deposition pressure 0.25 Pa to form a surface layer. By continuously changing the flow rates of Ar gas and O2 gas to form Ni oxide after the metal layer formation, a Ni oxide layer in which the Ni element content gradually increases and the O element content gradually decreases from the surface side toward the metal layer can be formed. That is, in Examples 2, 4 to 7, the lower electrode layer had a laminated structure of a metal layer made of a Ni layer and a Ni oxide layer made of a composition gradient layer provided on the Ni layer, in which the Ni element content and the O element content gradually change. In Table 1, NiO (gradient 50 nm) indicates that the Ni oxide layer is a compositionally graded layer with a thickness of 50 nm. Between the metal layer and the surface layer and in the surface layer, the Ni element content changed continuously, resulting in a seamless lower electrode layer.
[0079] [Example 3] A 100 nm Ni film was formed as a metal layer under the conditions of Ar gas 60 sccm, RF power 300 W, deposition pressure 0.25 Pa, and substrate temperature 350°C. Subsequently, a surface layer was formed by depositing a 50 nm Ni oxynitride film on the Ni layer under the conditions of RF power 500 W and deposition pressure 0.25 Pa while gradually decreasing Ar gas from 60 sccm to 30 sccm and gradually increasing O2 gas and N2 gas from 0 sccm to 15 sccm, respectively. After the metal layer was formed, the flow rates of Ar gas, O2 gas, and N2 gas were continuously changed to form a Ni oxide film, so that a Ni oxynitride layer in which the Ni element content gradually increases and the O element content and the N element content gradually decrease from the surface side toward the metal layer can be formed. That is, in Examples 2, 4 to 7, the lower electrode layer had a laminated structure of a metal layer made of a Ni layer and a Ni oxynitride layer made of a gradient layer in which the Ni element content gradually changes, provided on the upper layer. In Table 1, NiON (gradient 50 nm) indicates that the Ni oxynitride layer is a compositionally graded layer with a thickness of 50 nm. Between the metal layer and the surface layer and in the surface layer, the Ni element content changed continuously, resulting in a seamless bottom electrode layer.
[0080] -Orientation control layer- In Example 4, Ar was flowed on the lower electrode layer so that the substrate temperature was 500° C. and the deposition pressure was 0.8 Pa, and a BaRuO 3 film was deposited to a thickness of 10 nm as the orientation control layer. In Example 5, Ar was flowed on the lower electrode layer so that the substrate temperature was 500° C. and the deposition pressure was 0.8 Pa, and a 10 nm SrRuO 3 film was formed as the orientation control layer. The other examples and comparative examples did not include an orientation control layer.
[0081] -Piezoelectric film- [Comparative Examples 1 and 2, Examples 1 to 3] The target material was a Pb 1.3 (Zr 0.46 Ti 0.42 Nb 0.12A sintered body of Nb-doped PZT (hereafter referred to as N-PZT) was formed as a piezoelectric film under the conditions of a vacuum degree of 0.3 Pa, an Ar / O2 mixed atmosphere (O2 volume fraction 2.0%), an RF output of 500 W, and a substrate temperature of 600°C. The thickness of the piezoelectric film was 2 μm. [Examples 4 and 5] The target material was a Pb 1.15 (Zr 0.46 Ti 0.42 Nb 0.12 A sintered body of 0.1g / cm2 was used. The film was formed under the same film forming conditions as in Example 1, except that the substrate temperature was set to 550°C. [Example 6] Pb 1.3 (Zr 0.325 Ti 0.285 Nb 0.3 Ni 0.09 The deposition conditions were the same as in Example 1. [Example 7] Pb 1.3 (Zr 0.4125 Ti 0.3725 Nb 0.2 Sc 0.015 The deposition conditions were the same as in Example 1.
[0082] As described above, a laminate substrate was obtained in which a lower electrode and a piezoelectric film were laminated on a substrate. For each of the laminate substrates in the examples and comparative examples, a diffraction pattern was obtained by X-ray diffraction using an X-ray diffraction device manufactured by Malvern Panalytical, and it was confirmed that the piezoelectric film had a perovskite structure.
[0083] <Lower electrode layer element distribution measurement> The element distribution in the thickness direction of the lower electrode layer can be measured by SIMS (Secondary Ion Mass Spectrometry) analysis. As an example, data obtained by SIMS analysis using a sample having the lower electrode layer of Example 2 is shown in FIG. 6. The sample was subjected to Ar + The analysis was carried out while cutting the surface side of the Ni oxide layer by irradiating it with ions.
[0084] In FIG. 6, the horizontal axis indicates the position in the thickness direction of the lower electrode layer, with 0 being the surface position of the lower electrode layer, and the position to the right of the horizontal axis is closer to the substrate. As shown in FIG. 6, at the surface position of the lower electrode layer, the contents of both Ni and O elements were close to 50 at%. The content of Ni element gradually increased from the surface toward the substrate side, and reached approximately 100 at% at about 50 nm, showing a constant value. On the other hand, the content of N element gradually decreased from the surface toward the substrate side, and reached approximately 0 at% at about 50 nm, showing a constant value. It is clear that the lower electrode layer of Example 2 has a surface layer with a profile in which the contents of Ni and O elements gradually change in the thickness direction, as shown in FIG. 6, by gradually changing the flow rate ratio of Ar gas and O2 gas during surface layer deposition.
[0085] <Measurement of dielectric constant> (Preparation of measurement samples) The laminated substrate was diced into 1-inch (25 mm) squares to produce a 1-inch square piezoelectric laminate. With a metal mask with a circular opening of 400 μm in diameter placed on the piezoelectric film, a 100 nm thick ITO layer was sputtered. This resulted in a 1-inch square sample for dielectric constant measurement with a circular upper electrode layer of 400 μm in diameter at the center of the piezoelectric film surface.
[0086] (measurement) The dielectric constant was measured using an impedance analyzer manufactured by Agilent. An AC voltage with a frequency of 1 kHz was applied to the piezoelectric element of each example, and the dielectric constant was calculated from the measured impedance value. The obtained dielectric constants are shown in Table 1.
[0087] Comparative Example 1 is a piezoelectric element having a lower electrode layer made of Ir, which has been conventionally used, and is an example with a good dielectric constant. Table 1 also shows the ratio of the dielectric constant of each of the examples and comparative examples to the dielectric constant of Comparative Example 1.
[0088] <Driving stability test> For the drive stability (durability) test, a sample prepared for measuring the dielectric constant was used. In an environment of 150°C, the lower electrode layer was grounded and a voltage of -30V was applied to the upper electrode layer, and the time (hr) from the start of voltage application until dielectric breakdown occurred was measured. The measurement results are shown in Table 1. Dielectric breakdown was considered to have occurred when a current of 1 mA or more flowed through the piezoelectric element.
[0089] [Table 1]
[0090] In the case of Comparative Example 1, which has a lower electrode layer made of Ir, the dielectric constant is relatively high and favorable, but the durability is low and long-term reliability is lacking. In the case of Comparative Example 2, which has a lower electrode layer made of Ni, the dielectric constant is 10% or more lower than in Comparative Example 1, which has an Ir layer as the lower electrode layer, and it is clear that the piezoelectric characteristics are lower than those of conventional elements.
[0091] In Example 1, the lower electrode layer is provided with a metal layer made of Ni and a surface layer made of Ni oxide whose composition does not change in the thickness direction. In this configuration, the dielectric constant is higher than that of Comparative Example 1, and the durability is also significantly higher.
[0092] The piezoelectric elements of Examples 1 to 7 have a high dielectric constant compared to Comparative Example 1, or the decrease in dielectric constant is limited to within 4%, and it is clear that they have good piezoelectric properties. Furthermore, Examples 1 to 7 have significantly improved durability compared to Comparative Example 1. However, Example 1 is slightly inferior in durability compared to Examples 2 to 7. It is believed that in Examples 2 to 7, peeling is less likely to occur compared to Example 1 because the composition change in the lower electrode layer is continuous, and therefore, durability is improved.
[0093] In particular, the piezoelectric elements of Examples 4 and 5, which were provided with an orientation control layer, had a dielectric constant comparable to that of the piezoelectric elements provided with an Ir electrode layer, and also had a large improvement in durability. From Examples 2 and 3, it was found that the piezoelectricity and durability were improved more effectively when the surface layer of the lower electrode layer was a NiO gradient layer than when the surface layer was a NiON gradient layer.
[0094] In Examples 1 to 7, only Ni is used as the metal species in the lower electrode layer, and the material cost can be significantly reduced compared to the case where Ir is used. As shown in Examples 1 to 7, it is clear that the technology disclosed herein can provide a piezoelectric element that exhibits piezoelectric characteristics comparable to those of a conventional piezoelectric element using Ir in the lower electrode layer, has high reliability, and allows for a significant reduction in manufacturing cost. [Explanation of symbols]
[0095] 1, 1A, 1B Piezoelectric element 5, 5A, 5B Piezoelectric laminate 10 Substrate 11 Adhesion layer 12, 22 Lower electrode layer 12a, 22a Boundary of the lower electrode layer on the piezoelectric film side 12b, 22b surface layer 12c, 22c metal layer 22d Boundary between surface layer and metal layer 13 Orientation control layer 15 Piezoelectric film 18 Upper electrode layer
Claims
1. A piezoelectric laminate including a lower electrode layer and a piezoelectric film including a perovskite oxide, in this order, on a substrate, the lower electrode layer includes a metal layer containing Ni and a surface layer containing Ni oxide or Ni oxynitride; the surface layer of the lower electrode layer is disposed closest to the piezoelectric film, In the thickness direction of the surface layer, the content of Ni element changes in an increasing manner from the side closest to the piezoelectric film to the metal layer, and the change in the content is continuous, and the change in the content from the surface layer to the metal layer is continuous. Piezoelectric stack.
2. 2. The piezoelectric laminate according to claim 1, wherein the surface layer has a thickness of 20 nm to 60 nm.
3. 3. The piezoelectric stack according to claim 1, further comprising an orientation control layer between the lower electrode layer and the piezoelectric film, the orientation control layer including a metal oxide different from the Ni oxide.
4. The piezoelectric stack of claim 3 , wherein the metal oxide comprises at least one of Sr and Ba.
5. The piezoelectric stack according to claim 1 , wherein the perovskite oxide contains Pb, Zr, Ti and O.
6. The piezoelectric stack of claim 5 , wherein the perovskite oxide comprises at least one of Nb, Sc, and Ni.
7. The perovskite oxide is a compound represented by the following general formula (1): Pb{(Zr x Ti 1-x )1-yNb y }O 3 (1) 0<x<1, 0.1≦y≦0.4, The piezoelectric laminate according to claim 6 .
8. A piezoelectric laminate according to any one of claims 1 to 7, an upper electrode layer provided on the piezoelectric film of the piezoelectric laminate.
Citation Information
Patent Citations
Piezoelectric element and manufacture thereof
JP1996116101A
Piezoelectric element, ink delivering element and ink-jet type recorder
JP2003188429A
Piezoelectric element and manufacturing method thereof, electronic device, ink jet device
JP2007300071A
Piezoelectric film and piezoelectric element
JP2012009677A
Piezoelectric device, method for manufacturing the same, and light deflector
JP2018085478A